Learning Video Media Based on the Powtoon Application on Solar System Learning Topics - Sanjaya, Gede Edo Wahyu; Yudiana, Kadek; Japa, I Gusti Ngurah (International Journal of Elementary Education, 2021)
The lack of availability of innovative learning media that is able to contain material effectively results in low learning motivation and students' understanding of the material. It takes innovative learning media that can improve the quality of learning and create a more meaningful learning process for students. This development research aims to develop instructional video media based on the powtoon application on the topic of the 6th grade solar system whose validity has been tested. This development research uses the ADDIE model. The subjects in this study were instructional video media based on the powtoon application on the topic of the 6th grade solar system with the validity of the media as objects in the study. The data were collected using a questionnaire method and a rating scale instrument in the form of an assessment sheet given to 2 material experts, 2 media experts, and 2 practitioner experts to determine the validity of the powtoon application-based instructional video media on the topic of the solar system. The percentage of scores obtained was 84% and 88% from material experts, 80% and 86% from media experts, 89% and 87% from good predicate practitioners. So, based on this analysis, the instructional video media based on the powtoon application on the topic of the 6th grade solar system is valid and suitable for use in learning.